Rafting from the perspective of an interdisciplinary project with integrated High School (Research, Society and Development, 2021)
This article aims to report the experience with the elaboration and execution of an interdisciplinary project for classes of the 2nd year of integrated high school, in the view of the teachers involved in the process, having as a generator theme the experience of rafting (extreme sport). The experience is configured as qualitative and descriptive, with the locus of experience being the technical courses in a secretariat integrated to the high school of IFMT - Campus Cuiabá Cel. Octayde Jorge da Silva. The subjects were students enrolled in the two 2nd year classes of the 2019 school year, totaling 76 students involved. The presentation of the data followed the paths taken in the pedagogical sequence constructed and executed, being constituted from the collective elaboration of an interdisciplinary project, the development of the contents for each discipline involved, the challenges for the execution of the project, the experience of rafting and the interdisciplinary evaluation.